The Long Road to Social Inclusion: Participation of Vulnerable Groups in Village Development - Ro'fah, Ro'fah; Hanjarwati, Astri; Suprihatiningrum, Jamil (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2022)
The Indonesian village Law No. 6/2014 has set the tone for empowering local development, establishing village as a local democratic institution with the ability to manage its own development. It is explicitly stated in the law that one of its goals is to establish the village community as a subject instead of an object of development. Therefore, the law highly encourages civic participation. While the mechanism is in place to ensure the participation of village inhabitants, the participation of marginalized groups such as women, people with disabilities, and eldery remain unexplored. Using interviews with the marginalized groups in four villages in Indonesia, the aim of this paper seeks to capture the dynamic participation of this population and to examine the barriers to their participation in the development process. In this study, it was found that meaningful participation has not yet been achieved, thus, there is still a need to advocate for empowerment for this population. In addition, marginalized groups continued to experience challenges and barriers in to their participation, primarily due to the absence of a structure and mechanisms that specifically address their need. These include the absence of disability or women organizations or forums, the inaccessibility of information, and the lack of awareness of village government to include marginal groups.